The Effectiveness of CO2 Absorption Between Phytoplankton and Seagrass Beds in The West Sekotong Intertidal Zone of Lombok Island - Sri Puji Astuti; Ika Puspita Dewi; Siti Rosidah; Sari Novida; Eka S Prasedya; Dining A Candri; Hilman Ahyadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The increasing sea surface temperature could be approved CO2 levels on the coast. It has been assumed the primary productivity in the intertidal zone was to absorb CO2 from the water column for photosynthesis. In addition, the substrate floor has a potential source of CO2 from decomposers. Phytoplankton and seagrasses are the primary productivity in the intertidal zone. Both of them have chlorophyll, they maintain the CO2 as a carbon source to move the photosynthetic systems to develop the metabolism of the body's cells. The measurements were made of the leaves and rhizomes of all the seagrass species. The absorption process was clarified by measuring the growth rate, percent LOI, and percent carbon in the whole body of the Tetraselmis sp and Dunaliella sp, which were phytoplankton species isolated from seagrass ecosystems. Enhalus acoroides (Ea) had the highest carbon content. On the other hand, Halophila ovalis and Halophila minor are the lowest carbon due to the distribution of Ea being the widest, they were found in all of the sampling areas. In addition, the factor that was supported was due to its high growth rate ability. Phytoplankton and seagrass on the coast of Sekotong Barat absorb CO2 in the water column and floor of the sediment (carbon sink). The presence of a different increase in carbon content between Tetrasemis sp and Dunaliella sp indicates, the species of phytoplankton respond differently to CO2 stress in the ocean.